Prevalence, antimicrobial susceptibility patterns, and associated risk factors of species in healthcare and community settings in Ethiopia: a systematic review and meta-analysis - Zigale Hibstu Teffera; Wubetu Yihunie Belay; Bantayehu Addis Tegegne; Abebe Dagne; Adane Adugna; Habtamu Belew; Yasabe Leykun; Samrawit Tefera; Bewket Mesganaw Shtie; Abebe Yenesew; Abateneh Melkamu; Gashaw Azanaw Amare; et al. (Therapeutic Advances in Infectious Disease)
Background: Enterococci are significant contributors to healthcare-associated infections in Ethiopia. Objectives: This systematic review and meta-analysis synthesize data on the prevalence, antimicrobial susceptibility patterns, and associated risk factors for Enterococcus infections in Ethiopia Design: Systematic review and meta-analysis Data sources and methods: A comprehensive search was conducted in Scopus, PubMed, Web of Science, Cochrane Library, and Google Scholar, covering studies published in English over the past 5 years, with the last search on October 30, 2024. Inclusion criteria targeted original studies on Enterococcus prevalence, resistance, and risk factors in Ethiopian healthcare and community settings. Risk of bias was evaluated using the ROBINS-I tool. Meta-analytic techniques calculated pooled prevalence, log-adjusted odds ratios (log-AORs), and p -values, accompanied by heterogeneity and subgroup analyses. Results: Thirteen studies encompassing 3598 participants (mean age: 29.26 ± 6.6 years) reported a pooled prevalence of 6.67% (95% CI: 5.50–8.85) for Enterococcus species, with substantial regional variation (0.03–55.88). Major risk factors included prolonged hospital stays (OR = 6), catheterization (OR = 3.5), and diabetes (OR = 3.92). The pooled log-AOR was 0.986 (95% CI: 0.214–1.759; p  = 0.01). Antimicrobial susceptibility tests identified cephalexin and co-trimoxazole as the most effective antibiotics (100% sensitivity each), while oxacillin, trimethoprim-sulfamethoxazole, and norfloxacin exhibited the highest resistance rates (85.71%, 80.00%, and 80.00%, respectively). Considerable heterogeneity was observed ( I 2  = 92.31%, τ 2  = 5882.35). Conclusion: This systematic review and meta-analysis found a 6.67% pooled prevalence of Enterococcus infections in Ethiopia, with high variability in antibiotic resistance and key risk factors such as prolonged hospital stays, catheterization, and diabetes. Effective antibiotics included cephalexin and co-trimoxazole, while high resistance was noted for oxacillin and norfloxacin. The findings emphasize the need for targeted infection control and antimicrobial stewardship.